The languages ​​of education in Galicia in the last fifteen years - Callón Torres, Carlos Manuel (Avances en Supervisión Educativa, 2010)
This article is an outlook of the process of incorporation of the Galician language to teaching in the last fifteen years. The route begins from the passing of a minimal decree in 1995 and finishes with the re-enactment of a rule that reduces the presence of the Galician language and even forbids its use in some subjects this academic year, 2010/11.